Tourism Resilience to the Impact of the Covid-19 Pandemic in the Tourist Attraction of the Malino Pine Forest - Aditya Gowianto, Davin (Riviera Publishing, 2022)
Tourism is an activity of traveling with the aim of getting pleasure, seeking satisfaction, knowing something, improving health, enjoying sports or rest, fulfilling tasks, making pilgrimages and others. Indonesian tourism has also experienced significant development. Since the COVID-19 pandemic, tourist visits in South Sulawesi, including the Malino Pine Forest, have decreased. This research was conducted to find out more about the resilience of tourism in the Malino Pine Forest during the COVID-19 pandemic. This study uses 3 methods, namely semi-structured interviews, literature study and documentation. The sources of primary and secondary data are interviews with informants along with data on the number of tourist visits and also the income earned. And also using the basic concepts and theories of analysis, namely tourism, socio-economic and environmental impacts, pandemics, resilience, and resilience and tourism. The data will be analyzed using the SWOT analysis technique. Based on the data analysis carried out, there is a conclusion that tourism resilience in the Pinus Malino Forest is based on 2 factors, namely the health protocol carried out in the Malino Pine Forest to prevent the spread of COVID-19 and also their strategy to attract tourists' attention. The manager's strategy in dealing with this pandemic is to use social media such as Facebook and Instagram and also use the Word to Mouth method to promote the Malino Pine Forest to the wider community and in the SWOT analysis, the Malino Pine Forest has an internal and external environment that can strengthen resilience in the area. The Tourism Destinations. This resilience work pattern also protects the Malino Pine forest from the impact of the COVID-19 pandemic.